Can Innovation Strategy and Use of Technology affect Business Competitiveness? - Iffan, Muhammad (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
This research aimed at examining and analyzing the impact of Innovation Strategy and Use of Technology on Business Competitiveness. Methods used in this research was quantitative method using multiple regression, correlation coefficient, determination coefficient analysis, and hypothesis testing with validity and reliability test. Sampling method used in this research is saturated sampling through the distribution of questionnaires to 30 business actors at various distribution stores located in Bandung, Indonesia. The results showed that Innovation Strategy and Use of Technology have significant effect on Business Competitiveness simultaneously. Further research is also needed to understand whether Innovation Strategy and Use of Technology can affect other aspects besides Business Competitiveness such as business performance, business development, and business success.